Living Al-Qur’an and Hadith: The Application at SD Negeri Kenaran 2 - Minan, Muhammad Aufal; Rifai, Ikhsan; Naseh, Ahmad Hanany (Proceeding International Conference on Religion, Science and Education, 2022)
Al-Qur'an and Hadith are the main sources in Islam. It offers universal, humanist, dynamic, and contextual nature. Al-Qur'an and Hadith also offer a way of life for people who believe in it. Many thoughts about this matter such as asbabun nuzul, fiqh, tafsir, and so on. Although the Islamic world is very rich in the knowledge of the Qur'an and Hadith, there are still many studies that only dwell on the normativity of sacred texts. However, this study uses the concept of the historicity of the Qur'an and Hadith. In this case, the Qur'an and Hadith are placed in social phenomena. This research is called Living Al-Qur'an and Hadith. This research aims at how Muslims perceived the Qur’an and Hadith. The type of research is used qualitative-descriptive with a sociological approach. The research subjects were the community of SD Negeri Kenaran 2 in Prambanan, Sleman, Yogyakarta. After the data is collected, the data is explained through a normative approach to the sacred text. It aims to understand the historicity and its relationship with the normativity of sacred texts. The results showed that there were socio-religious phenomena. In that case, the school community perceives the Qur'an and Hadith as a way of life. The implication is that they can take the values contained in the Qur'an such as the Musabaqah Tilawatil Qur'an from the value of Surah Al-Baqarah verse 48, the duha prayer is inspired by Ad-Dzariyat verse 56 and the hadith narrated by Abu Dharr, and Asmaul Husna reading on Surah Al-A’raf verse 180.